The public shell: Vehicle for venture financing - Morgan, Alfred D (Journal of Business Venturing, 1988)
A public shell is generally defined as an inactive public corporation. It may or may not have assets or a publicly trading stock. However, for purposes here it must have valid SEC and domicile-State legal standing to permit its reactivation by merger with, or acquisition of, an operating company. After many years of clouded regard because of promoters' stock abuses, acceptance of using a shell to go public has considerably widened. This has been due to clarified and tighter SEC policies, rising costs of an IPO, and innovative financial uses of a shell by businessmen and investment bankers. Supply of shells probably still greatly exceeds demand for shells because of the mortality rate of the waves of new issues of recent years, the lack of cleanness of many of these shells and still lagging sophistication in their use. Nevertheless, advertising analysis indicates that in the past year alone companies "going public the back door" has at least trebled the number a decade ago. The greater part of this increase, also, appears to be accountable by ventures. For venture start-ups public access via merger with a shell can produce economies in legal/accounting costs and opportunity cost in time. It is also a means of becoming public when an initial public offering is not feasible due to market condition or nature of business. If the stock is trading it can encourage initial venture capital investment. The concept impact can vault the stock price even before earnings eventuate. Or exciting prospects can entice an exaggerated price/earnings ratio on tiny earnings. These events can even facilitate additional financing to prolong viability. But once the venture decides to use a shell for public access, the caveats of the route must be considered. In addition to valid registration and cleanness, such aspects as stockholder list, market sponsorship, control and dilution problems must be matched to the venture's financial aims. Cost of the shell can vary between $25,000-$100,000 depending on the outcome of these considerations, terms of payment, and general attractiveness of the venture entering the shell. Finally, speculative merits of shell stocks compared with the OTC Index of Industrial Stocks show that for equal holding periods, a market basket of revived-shell stocks bought soon after revival and sold around their highs, during the past decade would have produced multiple total returns compared to the less speculative index market basket. This optimum buy-sell period usually fell between 18 months and two years. But these returns presume not only sagacious timing, but that sales of stock of the typically small companies constituting shell-revivals could actually be made at the prices shown in the National Securities Dealers Pink Sheets. Beyond the optimum holding period, shell-descended companies become increasingly subject to valuation factors similar to those accorded to long established companies in related industries. © 1988.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-491-351-452-704 tex.type: [object Object]
Keywords: dept.fin